Highly efficient and color tunable thermally activated delayed fluorescent emitters and their applications for the solution-processed OLEDs. (April 2017) - Sun, Kaiyong; Sun, Yibai; Jiang, Wei; Huang, Suli; Tian, Wenwen; Sun, Yueming
Abstract: Here, some luminescent compounds, which comprise a central thianthrene-9, 9′, 10, 10′-tetraoxide acceptor core coupled with various donor units, have been synthesized and reported as thermally activated delayed fluorescent emitters. This set of compounds allows systematic fine-tuning of the band gap that cover the entire visible range from sky-blue to orange-red. The results of optical and electrochemical studies show that their highest occupied molecular orbitals and energy gaps can be easily modified by carefully choosing appropriate donor units. Solution-processed organic light emitting diodes with high maximum external electroluminescence quantum efficiencies of up to 9.1% have been demonstrated by using these emitters. Our results demonstrate the method that systematic tuning the band gap as well as keeping the suitable the lowest unoccupied molecular orbital energy levels of emitters is a promising strategy to achieve highly efficient full-color organic light emitting diodes. Graphical abstract: Highlights: Thianthrene-9, 9′, 10, 10′-tetraoxide based TADF emitters with various donor units has been synthesized. The emission spectra of the TADF materials can be fine-tuned from sky-blue to orange-red. The method is a promising strategy to achieve highly efficient full-color organic light emitting diodes.